(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, presents the results of the qualitative and quantitative composition of macro and microelements in the leaves and flowers of horseradish growing in Fergana region by the method of inductively coupled plasma mass spectrometry. According to the results of the analysis, the amount of 61 elements was determined in the leaves and flowers of horseradish. It was found that the amount of macro and microelements found in the leaves of horseradish is 2.5 times more than in its flowers. The amount of macroelements such as calcium, potassium, magnesium, sodium and phosphorus was determined, and it was found that calcium and potassium make up 87% of macroelements in leaves and 80% in flowers. Among the identified trace elements, iron, strontium, aluminum, manganese, boron, zinc, barium, copper, titanium, rubidium, lithium, molybdenum, nickel, cobalt, and chromium elements are relatively more abundant, iron leaves contain 70% of trace elements and it was found to be 50% in flowers. According to the conducted analysis, it was shown that the horseradish leaf is rich in calcium, potassium, magnesium, sodium, phosphorus and iron elements.